Struktur Fisik Arsitektur Tradisional Bali: Hubungan Unsur Struktur Fisik Dengan Hirarki Kesakralan Bangunan - Perpustakaan UGM, i-lib ([Yogyakarta] : Fak. Kedokteran Hewan UGM, 2000)
Until now there is no researcher to criticize deeply the physical structure of Balinese traditional architecture yet, especially relation between physical structure element to building hierarchy of sacredness, therefore this substance is feasible for the researched. Through an observation, literature study, and qualitative data analysis will be taken as a result namely: the physical structure of Balinese traditional architecture consist of the same element i.e: stereobate (bebaturan), pole with its stabilisator, and roof Stone material on the base is the genos element that is continuous, wood material on the top as a local colour. Hindu influence is created on padma ctructure. The higher strereobate (bebaturan) element, and the courtyard base of the building is the more sacred.